The Behavior of Exclusive Breastfeeding and Complementary Feeding (MP-ASI) as Causes of Stunting in Toddlers in Jombang: A Case Study - Rahmawati, Vivin Eka; Azizah, Ninik; Annuchasari, Helmi (Ahmar Metastasis Health Journal, 2024)
Exclusive breastfeeding, food preparation, and food sanitation are part of parental care patterns that also influence the occurrence of stunting. Stunting is a condition of impaired growth in toddlers due to chronic malnutrition, particularly during the first 1000 days of life. The issue of stunting in toddlers indicates chronic nutritional problems, influenced by many factors including the condition of the mother, the intranatal period, infancy or toddlerhood, and illnesses suffered during toddlerhood, as well as other issues that indirectly affect health. The purpose of this research is to explain and provide an understanding and interpretation of the internal dimension, namely the behavior of exclusive breastfeeding and complementary feeding for toddlers in Jombang District. This study uses a qualitative method with a case study approach conducted at the Health Office of Jombang Regency, East Java, and Mayangan Health Center. A total of 3 key informants, 11 mothers of toddlers as the main informants, and 1 supporting informant were selected purposively and by snowball sampling. Data collection was done using interviews, observations, and documentation. Data were analyzed using the Miles and Huberman approach. The results of the study indicate that parental education level, exclusive breastfeeding, and complementary feeding (MP-ASI) are among the factors causing stunting in Jombang Regency, East Java. The impact unrelated to the occurrence of stunting is parental occupation. There are several other internal and external factors causing stunting in Jombang Regency, East Java, such as parental education level, parental occupation, exclusive breastfeeding, and complementary feeding (MP-ASI).